No God, no God’s Eye: A Quasi-Putnamian Argument for Monotheism - Gafvelin, Åke (Conatus - Journal of Philosophy, 2021)
Metaphysical realism is the thesis that “the world consists of some fixed totality of mind-independent objects” such that “there is exactly one true and complete description of ’the way the world is’”. In the first part of this essay, I will present Hilary Putnam’s worry with metaphysical realism. Secondly, I will argue that metaphysical realists must commit to metaphysical anthropocentrism in order to solve Putnam’s problem. Thirdly, I will argue that metaphysical anthropocentrism requires monotheism. Lastly, I argue that metaphysical realism is true. Therefore, we must be ontologically committed to God.